CUSTOMER SATISFACTION ANALYSIS IN INFORMATION CENTER: A CASE STUDY AT SEMARANG CONTEMPORARY ART GALLERY - Siti Safingah; Nila Arofa’ina; Dr. Nor Erlissa Abd Aziz; Assoc. Prof. Ts. Dr. Ghazali Osman; Noor Arina Md Arifin (International Journal of Accounting, Finance and Business, 2023)
This paper has discussed customer satisfaction in an information center called Semarang Contemporary Art Gallery. The methods that have been used are interviews with gallery managers and literature studies which are relevant to this topic. The results showed that the Semarang Contemporary Art Gallery needs some attention to customer satisfaction. The findings also showed that the implementation of service quality is quite good. However, the level of customer satisfaction is still not optimal, which has caused the inability to measure customer satisfaction with the service provided. At the same time, customer satisfaction is one of the most important elements in the operation of the information center. This paper has discussed the insight of the readers, especially readers who manage information centers so that they do not forget the importance of customer satisfaction in an information center.